Investigating Symbols and Messages in The Song and Music Video of Paramore’s “Brick By Boring Brick” Using Peirce’s Triadic Analysis - Abdullah Abdullah; Imran Said Yusuf (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
This semiotic analysis used Peirce’s triadic theory to interpret the symbols contained in the lyrics and music video of Paramore entitled “Brick by Boring Brick”. The research applied descriptive qualitative method to reach the needed results. There are sixteen signs interpreted either in general interpretation or referred to fairy tales. By interpreted those signs we gain the intended message that the songwriter wanted to deliver, those signs mentioned symbols like “Taste and smells” which meant the essence of the world. Also “Brick by boring brick” which referenced to the fairy tale of “Three little pigs” and fourteen more symbols interpreted in this research. The message which the songwriter tried to spread was for people to stopped dreaming a life just like in fairy tales which was always end in a beautiful ever-after and started learning to live in the reality. A life like in fairy tales are not real and better stopped trying to impress people and start improving instead.